2016
DOI: 10.1042/bcj20160387
|View full text |Cite
|
Sign up to set email alerts
|

Gsk3β and Tomm20 are substrates of the SCFFbxo7/PARK15 ubiquitin ligase associated with Parkinson's disease

Abstract: Fbxo7 is a clinically relevant F-box protein, associated with both cancer and Parkinson's disease (PD). Additionally, SNPs within FBXO7 are correlated with alterations in red blood cell parameters. Point mutations within FBXO7 map within specific functional domains, including near its F-box domain and its substrate recruiting domains, suggesting that deficiencies in SCFFbxo7/PARK15 ubiquitin ligase activity are mechanistically linked to early-onset PD. To date, relatively few substrates of the ligase have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 69 publications
1
47
0
Order By: Relevance
“…FBXO7 negatively regulates glycogen synthase kinase 3 β (GSK3β) activity. FBXO7 ubiquitinates translocase of outer mitochondrial membrane 20 (Tomm20), and its levels correlate with Fbxo7 expression, indicating a stabilizing effect [69]. DJ-1, the product of the causative gene of a familial form of PD, plays a significant role in anti-oxidative defense to protect cells from oxidative stress.…”
Section: Pathogenic Mechanismsmentioning
confidence: 99%
“…FBXO7 negatively regulates glycogen synthase kinase 3 β (GSK3β) activity. FBXO7 ubiquitinates translocase of outer mitochondrial membrane 20 (Tomm20), and its levels correlate with Fbxo7 expression, indicating a stabilizing effect [69]. DJ-1, the product of the causative gene of a familial form of PD, plays a significant role in anti-oxidative defense to protect cells from oxidative stress.…”
Section: Pathogenic Mechanismsmentioning
confidence: 99%
“…SCF Fbxo7 ubiquitinates GSK-3β in a K63-dependent manner and Fbxo7 represses its activity. In contrast, Fbxo7 stabilizes TOM20 and correlates with its levels [20]. These indicate a connective network that is a novel field for further investigation.…”
Section: Gsk-3β Regulates Mitochondrial Biogenesismentioning
confidence: 99%
“…Teixeira and colleagues identified the mitochondrial protein translocase of outer mitochondrial membrane 20 (TOM20) in a ubiquitination target screen and validated TOM20 as a bona fide substrate of FBXO7 (Teixeira et al . ). The authors reported ubiquitin modification of TOM20 by FBXO7 (Teixeira et al .…”
Section: Fbxo7 and Mitochondrial Clearancementioning
confidence: 97%
“…The authors reported ubiquitin modification of TOM20 by FBXO7 (Teixeira et al . ), but TOM20 also responds to the presence of the E3 ligase parkin upon CCCP treatment (Chan et al . ).…”
Section: Fbxo7 and Mitochondrial Clearancementioning
confidence: 99%
See 1 more Smart Citation